ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK KELAS XI SMA PADA MATERI SISTEM EKSKRESI - Rintan Rahmana Sari; Lufri Lufri; Ganda Hijrah Selaras; Rahmawati Darussyamsu (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Implementation of the 2013 curriculum is able to create students who have the ability to think at a higher level as the demands of the age to come. Students are expected to be able to think critically, creatively, and innovatively. One effort to improve students higher order thinking skills is to get students used to working on high level thinking skills. This research was conducted in October 2019 at SMAN 1 Kec. Kapur IX. The subjects in this study are the assessment instruments commonly used by teachers in school and the higher order thinking assessment instruments developed by the authors. The assessment instruments were tested on 24 students of Class XI MIPA 1 SMAN 1 Kec. Kapur IX. This type of research is a descriptive study that aims to analyze students higher-order thinking skills on the material excretion system using assessment instruments. The results of the analysis revealed that students high-level thinking skills were relatively low, This was evidenced by the results of the test of the questions obtained in the form of an average grade of 48. 17. The low cognitive level on the assessment instruments made by the teacher is one of the reasons for the low level of thinking ability of students. This causes students not accustomed to working on high-level thinking skills.